Why Don't Prices Rise During Periods of Peak Demand? Evidence from Scanner Data - Chevalier, Judith A; Kashyap, Anil K; Rossi, Peter E (American Economic Review, 2003)
We examine retail and wholesale prices for a large supermarket chain over seven and one-half years. We find that prices fall on average during seasonal demand peaks for a product, largely due to changes in retail margins. Retail margins for specific goods fall during peak demand periods for that good, even if these periods do not coincide with aggregate demand peaks for the retailer. This is consistent with “loss-leader” models of retailer competition. Models stressing cyclical demand elasticities or cyclical firm conduct are less consistent with our findings. Manufacturer behavior plays a limited role in the countercyclicality of prices.